Bacteriology of the conjunctiva in pre-cataract surgery patients with occluded nasolacrimal ducts and the operation outcomes in Japanese patients. Issue 1 (December 2017) - Hayashi, Yuko; Miyamoto, Takeshi; Fujita, Shuko; Tomoyose, Katsuo; Ishikawa, Nobuyuki; Kokado, Masahide; Sumioka, Takayoshi; Okada, Yuka; Saika, Shizuya
Abstract Background Contamination of the conjunctiva in association with nasolacrimal duct obstruction is by all accounts a risk factor for infectious endophthalmitis post-cataract surgery. Methods All patients who underwent cataract day surgery routinely received nasolacrimal duct syringing with normal saline at the Wakayama Medical University Hospital, Japan, from 2011 to 2013. The microorganisms isolated from conjunctival swab samples of patients with occluded nasolacrimal ducts and their susceptibility to antibiotics, as well as the operation outcomes in all the patients were retrospectively investigated. Results Nasolacrimal duct obstruction was observed in 125 eyes of 90 patients (3.3%; 42 eyes of 30 male individuals, and 83 eyes of 60 female individuals) from a total of 3754 eyes of 2384 patients by using irrigation samples of nasolacrimal ducts. The mean age of the subjects with duct obstruction was 79 ± 8.5 years.. In bacterial cultures of swabs from these 125 individuals, microbial growth was detected in 56 samples (i.e. 44.8%). Coagulase-negativeStaphylococcus was detected in 28 eyes, andCorynebacterium species was detected in 17 eyes.Staphylococcus aureus, excluding methicillin-resistantS. aureus was detected in seven eyes with nasolacrimal duct obstruction. Methicillin-resistantS. aureus was isolated in two eyes with nasolacrimal duct obstruction. Each case was treated with topical antibiotics based on the results of antibiotic sensitivity tests. After culturing of cotton swab samples from the conjunctiva, and using direct micrography of bacteria every 2 or 3 days after starting treatment, and once the results were negative (consecutively tested three times), the patients received cataract surgery. In the current case series, bacteria were not detected in conjunctival swabs obtained consecutively three times for 3 weeks after starting topical antibiotics in 118 eyes from 125 eyes (94.4%), and later in the remaining patients. No patient required dacryocystorhinostomy to eliminate bacterial contamination in the conjunctiva following topical antibiotic therapy. No patient developed infectious endophthalmitis at least 1-year post-cataract surgery. Conclusions All the patients receiving cataract day surgery underwent the operation after the elimination of conjunctival microorganism contamination in association with nasolacrimal duct obstruction by using appropriate topical antibiotics.